Investigation Of Practical And Simple Design Procedure For Robust Control Of A Pneumatic Muscle Actuated System - Chong, Shin Horng; Abdul Rahim, Ruzairi; Md Ghazaly, Mariam; Jaafar, Hazriq Izzuan; Shukor, Ahmad Zaki; Mohd Mokhtar, Rosmiwati (UTeM, 2017)
Pneumatic muscle actuator (PMA) becomes famous and widely used in industrial automation process and medical applications (such as exoskeleton for rehabilitation), due to its power-to-weight ratio. Unfortunately, the major challenge in controlling PMA precisely is due to the problem of high nonlinear and its time varying characteristics. In practice, it is difficult to estimate correctly the model parameters, which governs the dynamics of a pneumatic actuator. Thus, a practical control which has a simple design procedure and capable to demonstrate high positioning and robust performance is needed to overcome the above-mentioned problem. The proposed practical control emphasizes a simple design procedure that does not acquire plants parameter modeling process, and yet is able to demonstrate high robustness and accuracy performance. The practical control, namely nominal characteristic trajectory following control, will be started by measuring experimentally the responses in open-loop. By constructing the responses, the behavior of the PMA system is indirectly included as a nonlinear element. The constructed-model, namely nominal characteristic trajectory (NCT) will act as a virtual velocity for the object motion, that tend to enhance the robustness performance of the PMA system. A proportional integral control will be designed and cascaded to the controller in order to make the mechanism follow the virtual movement, which is important to achieve high accuracy performance. The proposed practical controller is expected to perform high robustness and accuracy as a nonlinear controller, but can be designed as simple as linear controller. The primary contribution of this research includes a novel design procedure of a practical control, that does not require exact or known model parameters of the object, in order to enhance the robustness performance and accuracy in positioning control of a PMA system. The performance of proposed controller with PMA system will be validated experimentally for point-to-point and tracking motion performance.